Shall we share? Platforms and institutional challenges in the sharing economy - Sousa, C.; Ferreiro, Maria de Fátima; Vale, S. (7º Encontro anual de Economia Política, 2024)
Sharing things has been around since the dawn of civilisation, but people used to share their things only with family and friends (Böcker & Meelen, 2017; Ranjbari et al., 2018). The sharing economy has rocketed in the last decade as a result of the widespread adoption of digital technologies and platforms that enable peer-to-peer exchange of goods with strangers (Frenken & Schor, 2017). The growth of the “sharing economy” has been triggered by factors other than technology, namely globalisation, the global economic crisis, changes in consumer attitudes and greater attention to sustainability in consumption (Hamari et al., 2016). The latter, has been a driving factor in some contexts, mainly linked to the idea of ecologically sustainable consumption (Hamari et al., 2016; Tussyadiah, 2016), derived from growing skepticism towards capitalist structures and anti-consumerism movements. In this sense, participating in sharing initiatives is seen as taking part in alternative forms of green, ethical, or sustainable consumption, which are becoming increasingly important in people's daily lives (Möhlmann, 2015). However, is a growing debate about the effectiveness of the sharing economy to fulfil these promises (Codagnone & Martens, 2016), namely due the widespread use of some sharing platforms. This has also stressed the need to discuss regulation and other institutions. For example, some governments are introducing regulations to ensure the security of all actors, to address negative externalities and to collect taxes (Bentkowska, 2021). In this context, the growth of the sharing economy poses significant challenges for the existing institutional frameworks that regulate markets and social interactions. In particular, institutions play a crucial role in promoting trust, facilitating cooperation, reducing transaction costs, and creating markets for the sharing economy. This paper examines how institutions, such as regulations, norms, trust and reputation, evolve in the context of the sharing economy and influence the creation of markets and the use of technological platforms. It reviews the literature on the sharing economy and institutions and proposes a conceptual framework for analyzing their evolution and dynamics. The framework consists of three dimensions: (1) types of sharing platforms; (2) governance of the platforms; and (3) benefits and their distribution. The paper also applies this framework to a set of cases described in the empirical literature and identifies the main challenges and opportunities for future research on this topic